Separate waste collection in higher education institutions with its technical and social aspects: A case study for a university campus - GÜRSOY HAKSEVENLER, BETÜL HANDE; AKPINAR, AYDIN (My University, 2022)
As universities are considered living laboratories with the practical learning of today\"s students and tomorrow\"s decision makers, practitioners, as well as parents, it is important to understand to what extent separate waste collection can be achieved in universities. This study aims to determine the amount, composition, and recycling potential of the generated waste in the Marmara University Anadoluhisari campus in Turkey, in order to develop a waste management strategy in line with national legislation and sustainable global practices. In addition, this study aims to evaluate the knowledge, awareness, behavior, and motivation of campus stakeholders towards this strategy. A separate waste collection application was carried out on the campus. In order to determine the amount of mixed waste before this application and the amount of fractionated waste after this application, daily waste weighing was carried out in certain periods between November 04, 2019 and November 01, 2020. For the social aspect of the study, a survey was conducted on campus students, administrative officers and academic personnel studying and working at different faculties. From the technical aspect, it was found that the recycling potential of campus waste was high (69%). However, when the social aspect of the study was examined, it was determined that only 16% of campus occupants had knowledge of Zero Waste Regulation. Furthermore, none of the group felt directly responsible for separated waste collection. Only 26% of the campus population, who carried out this practice on campus, stated that waste is separately collected on campus. Based on plastic bottle discarding behavior reported, only 16% of participants were found to be very conscious about waste recycling. It was concluded that recyclable waste separation was carried out by students who were unaware of its purpose. Among the studied groups, the academic personnel were relatively more conscious than the other groups. Ac-cording to campus stakeholder\"s opinions, incentives and basic education were the main factors for improving solid waste management.
Keywords: Tarımsal Bilimler; Çevre Mühendisliği; Mühendislik ve Teknoloji; Agricultural Sciences; Environmental Engineering; Engineering and Technology; YEŞİL VE SÜRDÜRÜLEBİLİR BİLİM VE TEKNOLOJİ; Çevre / Ekoloji; Tarım ve Çevre Bilimleri (AGE); MÜHENDİSLİK, ÇEVRE; Mühendislik; Mühendislik, Bilişim ve Teknoloji (ENG); ÇEVRE BİLİMLERİ; GREEN & SUSTAINABLE SCIENCE & TECHNOLOGY; ENVIRONMENT/ECOLOGY; Agriculture & Environment Sciences (AGE); ENGINEERING, ENVIRONMENTAL; ENGINEERING; Engineering, Computing & Technology (ENG); ENVIRONMENTAL SCIENCES; Atık Yönetimi ve Bertarafı; Kirlilik; Doğa ve Peyzaj Koruma; Çevre Kimyası; Çevre Bilimi (çeşitli); Genel Mühendislik; Mühendislik (çeşitli); Su Bilimi; Fizik Bilimleri; Yaşam Bilimleri; Waste Management and Disposal; Pollution; Nature and Landscape Conservation; Environmental Chemistry; Environmental Science (miscellaneous); General Engineering; Engineering (miscellaneous); Aquatic Science; Physical Sciences; Life Sciences; Awareness; Behavior; Motivation; University campus; Waste recycling potential; Separate waste collection; MUNICIPAL SOLID-WASTE; DEVELOPING-COUNTRIES; MANAGEMENT; SUSTAINABILITY; STUDENTS; BEHAVIORS; CHINA